A post occupancy evaluation of students’ hostels accommodation - Oladiran, O.J. (Penerbit UKM, 2013)
Hostel accommodation is very crucial to the performance of students. A post occupancy evaluation (POE) of existing hostels could foster their improvement and services. This study focuses on POE of students’ hostel accommodation in the University of Lagos, Nigeria. The problem of the study is specifically concerned with investigating the availability of students’ hostel accommodation and the satisfaction derived by the users. The objectives of the study are to investigate students’ hostel accommodation and their users’ satisfaction, to examine the additional facilities provided in the hostels, to pinpoint the problems of the users and that of the facilities managers in managing the hostels. The population of the study is the students of the University of Lagos and the facility managers; while the sampling frame is the students resident in the institution-owned hostels and the facility managers of such hostels in the main campus of the University. Eleven hostels were used and random sampling technique was used to a select a sample of 179 from the frame. Descriptive and inferential statistics tools were used to analyze the data. The study reveals that the content of hostels accommodation in the University of Lagos includes bathrooms, common rooms, bedrooms, reading rooms, kitchen and fixtures. There is also a sparse availability of laundry, pantry and meeting room in some of the hostels. The level of satisfaction of the users with the hostels accommodation is “good” in term of noiselessness, indoor temperature, natural lighting, ventilation and water supply; while it is “fair” with electrical fittings, space, cleanliness and comfortability. The study recommends that more accommodation with state of the art facilities should be provided in the University of Lagos.